Hybrid micro/nanostructural surface offering improved stress distribution and enhanced osseointegration properties of the biomedical titanium implant. (March 2018) - Hou, Ping-Jen; Ou, Keng-Liang; Wang, Chin-Chieh; Huang, Chiung-Fang; Ruslin, Muhammad; Sugiatno, Erwan; Yang, Tzu-Sen; Chou, Hsin-Hua
Abstract: Objectives: The aim of the present study was to investigate the surface characteristic, biomechanical behavior, hemocompatibility, bone tissue response and osseointegration of the optimal micro-arc oxidation surface-treated titanium (MST-Ti) dental implant. Materials and methods: The surface characteristic, biomechanical behavior and hemocompatibility of the MST-Ti dental implant were performed using scanning electron microscope, finite element method, blood dripping and immersion tests. The mini-pig model was utilized to evaluate the bone tissue response and osseointegration of the MST-Ti dental implant in vivo . Data were analyzed by analysis of variance using the Student's t- test ( P ≤ 0.05). Results: The hybrid volcano-like micro/nanoporous structure was formed on the surface of the MST-Ti dental implant. The hybrid volcano-like micro/nanoporous surface played an important role to improve the stress transfer between fixture, cortical bone and cancellous bone for the MST-Ti dental implant. Moreover, the MST-Ti implant was considered to have the outstanding hemocompatibility. In vivo testing results showed that the bone-to-implant contact (BIC) ratio significantly altered as the implant with micro/nanoporous surface. After 12 weeks of implantation, the MST-Ti dental implant group exhibited significantly higher BIC ratio than the untreated dental implant group. In addition, the MST-Ti dental implant group also presented an enhancing osseointegration, particularly in the early stages of bone healing. Conclusion: It can be concluded that the micro-arc oxidation approach induced the formation of micro/nanoporous surface is a promising and reliable alternative surface modification for Ti dental implant applications.